KP hierarchy and (1+1)-dimensional multicomponent integrable systems - Sidorenko, Yu. M. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
New types of reduction of the Kadomtsev-Petviashvili (KP) hierarchy are considered on the basis of Sato's approach. As a result, we obtain a new multicomponent nonlinear integrable system. Bi-Hamiltonian structures for the new equations are presented.